Proximate and mineral composition of whole and dehulled Nigerian sesame seed - Bamigboye, Adeola Yewande; Okafor, Augusta Chinyeaka; Adepoju, Oladejo Thomas (Global Journal of Food and Agribusiness Management, 2011)
Sesame plant seed which grows extensively in Benue State of Nigeria is an important and popular source of edible oil. It ranks ninth among the top thirteen oilseed crops which make up 90% of the world production of edible oil. The relative abundance of its seed coupled with the little knowledge on its nutritional significance prompted the need for this study. Whole and dehulled Sesame seeds were studied for their proximate and mineral composition using standard methods of analyses of AOAC. The results of analyses revealed that 100g portion of seed sample contained 5.2 and 6.4 g moisture, 11.6 and 17.1g crude protein, 48 and 44g crude lipid, 4.6 and 2.6g crude fibre, 6.2 and 3.6g ash, 29.0 and 21.7g carbohydrate for whole and dehulled seed samples respectively. Both whole and dehulled seed samples were low in macrominerals but can be good source of both iron and zinc. The seed can be a good source of dietary protein, fibre, iron and zinc, apart from being a good source of edible oil.